Families, fortunes, and footwear : reaching out to the fourth generation of Brazil's Lupo S.A. - Ward, John; Zsolnay, Carol Adler; Waikar, Sachin (London : SAGE Publications Ltd, 2017)
A successful third-generation family business explores whether or not to continue in business as a family into the fourth generation. If they do decide to move forward as a family business, how can they cultivate knowledge and interest among the forty-plus fourth-generation family members?
Originally published: Ward, J., Waiker, S., & Zsolnay, C. A. (2009). Families, fortunes, and footwear: Reaching out to the fourth generation of Brazils Lupo S.A. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Lupo S.A.; Family-owned business enterprises -- Succession -- Brazil -- Case studies; Business planning -- Brazil -- Case studies; Clothing trade -- Brazil -- Case studies; Retail trade -- Brazil -- Case studies